menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Solve the equation. y + 6 = –3y + 26 y = –8 y = –5 y = 5 y = 8
asked
Feb 17, 2021
22.8k
views
1
vote
Solve the equation.
y + 6 = –3y + 26
y = –8
y = –5
y = 5
y = 8
Mathematics
high-school
Justin Lam
asked
by
Justin Lam
5.4k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
3
votes
Answer:
C
Explanation:
EDGE
BillmanH
answered
Feb 18, 2021
by
BillmanH
5.1k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
0
votes
Answer:
y=5
Explanation:
Alvaro Torrico
answered
Feb 21, 2021
by
Alvaro Torrico
5.4k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.7m
questions
7.4m
answers
Other Questions
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
1/7 + 3/14 equivalent fractions
185g in the ratio 2:3
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org